The Success of Thread-embedding Therapy in Generating Hair Re-growth in Mice Points to Its Possibly Having a Similar Effect in Humans - Hyun Jong Shin; Dong-Jin Lee; Kang Kwon; Hyung-Sik Seo; Han-Sol Jeong; Ji-Yeon Lee; Ki-Tae Ha; Chang-Hyun Lee; Yong-Suk Jang; Byung-Wook Lee; Byung Joo Kim; Myeong-Ho Jung (Korean Pharmacopuncture Institute, 2015)
Objectives: Recently, thread-embedding therapy (TET) has been widely applied in Korean medicine for cosmetic purposes such as reducing skin wrinkles. An inserted thread was reported to have induced continuous stimulation, followed by support for connective tissue regeneration. However, the potential role of TET in hairgrowth has not yet been reported. Methods: We designed this study to evaluate whether TET has a hair-growth-promoting effect. C57 black 6 (C57BL/6) mice were divided into three groups: normal saline-treated, minoxidil-treated, and thread-embedded groups. Normal saline or 5% minoxidil was topically sprayed on the dorsal skin of the mice once a day for 16 days. Medical threads were embedded into the dorsal skin of the mice in a single application. Hair growth activity was evaluated by using dermoscopic and microscopic observations. Sections of the dorsal skin were stained with hematoxylin and eosin. Expressions of bromodeoxyuridine (BrdU), proliferating cell nuclear antigen (PCNA), fibroblast growth factor-7 (FGF-7), and fibroblast growth factor-5 (FGF-5) were detected by using immunohistochemical staining. A reverse transcription-polymerase chain reaction (RT-PCR) analysis was adopted to measure the messenger RNA (mRNA) expressions of FGF-7 and FGF-5. Results: TET enhanced anagen development in the hair follicles of C57BL/6 mice. The expressions of BrdU and PCNA, both of which imply active cellular proliferation, were increased by using TET. Moreover, TET increased the expression of FGF-7, an anagen-inducing growth factor, while decreasing the expression of FGF-5, an anagen-cessation growth factor, both at the protein and the mRNA levels. Conclusion: TET enhanced hair re-growth in C57BL/6 mice. TET regulated the expressions of anagen-associated growth factors and activated the proliferation of hair follicular cells in depilated skin lesions. Considering its long-lasting effect, TET may be a good alternative therapeutic for the treatment of alopecia.